CONSUMPTION OF COMMERCIALLY AVAILABLE VITAMIN D FORTIFIED FOODS AND SUPPLEMENTS AMONG MUSLIM WOMEN IN COIMBATORE CITY - B. HABEEBA*; C.A. KALPANA (The Journal of Research ANGRAU, 2021)
Vitamin D fortification is an effective method to address the burden of Vitamin D deficiency worldwide. The effectiveness of fortification greatly depends on the availability and consumption of fortified foods. Thus, the study aims to identify commercially available Vitamin D fortified foods and supplements and their consumption among muslim women in Coimbatore city. In a market survey of 76 stores, selected by random sampling, data on the availability of fortified foods, cost, type and quantity of Vitamin D were recorded. Muslim women (n=225) between the age of 20–45 years were selected as respondents. Details on their demographic profile, health status, knowledge of Vitamin D, and consumption of fortified foods were collected. The findings revealed that 76 Vitamin D fortified products were available. Among these products, cereals and eggs provided >30 percent RDA of Vitamin D. A positive correlation existed between Vitamin D content and cost (P<0.05). Awareness about Vitamin D was very low among the women (3.6% to 7.7%). A moderately significant (p=0.052) association was observed between availability and consumption. Hence, an increase in awareness to promote the consumption of commercially available fortified foods is essential to combat Vitamin D deficiency.